Measuring Innovation Oriented Activities for Business Services: Traditional versus Knowledge Based Indicators - Michael Steiner (European Regional Science Association (ERSA), 2001)
Measuring Innovation Oriented Activities: Traditional versus Knowledge Based Indicators and their Differences across Sectors Michael STEINER, Christoph ADAMETZ, Mirjam NOVAKOVIC, Institute of Technology and Regional Policy, JOANNEUM RESEARCH, Elisabethstrasse 20/II, 8010 Graz, Austria and Department of Economics, Karl-Franzens-Universität Graz, Universitätsstraße 15/4, 8010 Graz E-Mail: michael.steiner@joanneum.ac.at , christoph.adametz@joanneum.ac.at, mirjam.novakovic@joanneum.ac.at Indicators and traditional methods for valuating productivity and innovation in the manufacturing sector are only to a limited degree applicable to business services. The internal innovation and knowledge organisation in services is as a rule only weakly formalized; in contrast to manufacturing firms, business services mostly do not have e.g. an organised research and development unit. Therefore quantitative indicators such as investments and employees in R&D or patents may give a distorted picture. Other factors such as human resources and their qualification, investment on “intangible assets” have gained increasing significance but are up to now hardly available for empirical analyses. For the first time a survey on a regional level tried to quantify the knowledge-base of Styrian firms by means of the qualification level, e.g. the share of academics, technicians and engineers. With this “new%94 innovation-indicator hidden technological innovation potentials can be revealed. In this paper we first want to give a short survey on to the differences between sectors regarding the usefulness of different innovation related indicators. We then analyse by using the above mentioned survey to what degree outcomes differ between traditional indicators measuring innovation activities and unconventional indicators such as the “technological knowledge base” in and between sectors. Furthermore we discuss additional approaches of measuring innovation in services. Key words: measuring innovation , service sector, technological knowledge base
Keywords: 330